Pile foundation response to ground vibration from rock blasting - Jayasinghe, Laddu Bhagya (2017)
Ground vibrations from blasting are undesirable and they are very short in duration with high principal frequencies and high amplitude. Structural response to that kind of excitations may differ significantly from that generated by lower-frequency earthquake vibrations. In practice, the damage to nearby structures to generated ground vibrations has been controlled by various codes and regulations available. However, the existing vibrations limits are not always applicable, as they depend on the geological conditions of the site and the dynamic characteristics of the structure. This paper investigated the influence of the rock-soil interface on the response of pile foundation to ground-borne vibration from rock blasting, through numerical simulations using finite element software LS DYNA. It is found that the slope of the rock-soil interface greatly influences the location of damage and the extent of damage on the pile. The bottom of the pile is subjected to a larger blast pressure and stresses are highly concentrated at the pile bottom. Thus, the pile bottom can fail in shear before it reaches its plastic moment capacity.